Synchronization analysis for a class of genetic oscillator networks - Gao, Q.; Du, J.; Liu, X. (Нелінійні коливання, 2017)
The paper deals with a synchronization problem for genetic oscillator networks. The genetic oscillators are modeled as nonlinear systems of Lur’e type. Simple and verifiable synchronization conditions are presented for genetic oscillator networks by using the absolute stability theory and matrix theory. A network composed of coupled Goodwin models is used as an example for numerical simulation to verify the effectiveness of the theoretical method. Розглянуто задачу синхронiзацiї мереж генетичних осциляторiв. Генетичнi осцилятори моделюються нелiнiйними системами типу Лур’є. Умови синхронiзацiї, якi є простими та якi можливо перевiрити, отримано для мереж генетичних осциляторiв iз використанням теорiї абсолютної стiйкостi та теорiї матриць. Мережа, що складається зi зв’язаних моделей Гудвiна, використовується як приклад для числових обчислень, якi пiдтверджують ефективнiсть теоретичного методу.